2005
DOI: 10.1128/aac.49.2.690-698.2005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Subtypes of Ciprofloxacin-Resistant Campylobacter spp. in Commercial Poultry Flocks before, during, and after Treatment with Fluoroquinolones

Abstract: Five commercial broiler chicken flocks were treated with either difloxacin or enrofloxacin for a clinically relevant infection, as instructed by a veterinarian. Campylobacters were isolated from individual fecal samples and from samples associated with the broiler environment before, during, and after treatment. Ciprofloxacinresistant Campylobacter jejuni and/or C. coli strains were detected pretreatment in four flocks, but they constituted a very small proportion of the campylobacters present. When the broile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 34 publications
2
68
1
1
Order By: Relevance
“…was observed on broiler flocks prior to treatment and the percentage of FQ-resistant isolates increased during treatment with FQ. The FQ-resistant Campylobacter subtypes which emerged either during or after treatment did not necessarily belong to the same subtypes which had been prevalent before treatment [5]. Though drugs had never been used on the flocks studied, fluctuation of antimicrobial resistant C. jejuni isolates was observed in the present study.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…was observed on broiler flocks prior to treatment and the percentage of FQ-resistant isolates increased during treatment with FQ. The FQ-resistant Campylobacter subtypes which emerged either during or after treatment did not necessarily belong to the same subtypes which had been prevalent before treatment [5]. Though drugs had never been used on the flocks studied, fluctuation of antimicrobial resistant C. jejuni isolates was observed in the present study.…”
mentioning
confidence: 56%
“…A similar change of the predominant clone [13] and the colonisation phenotypes [20] in chickens were reported. Humphrey et al [5] have reported that a small proportion of FQresistant Campylobacter spp. was observed on broiler flocks prior to treatment and the percentage of FQ-resistant isolates increased during treatment with FQ.…”
mentioning
confidence: 99%
“…strains isolated from poultry reveals the impact of the use of these antibiotics in poultry production (ENDTZ et al, 1991;SMITH et al, 1999;ENGBERG et al, 2004;HUMPHREY et al, 2005). Resistance levels vary according to the country, variable factors including the permission to use this drug in poultry production (CHEN et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial strains were isolated between 2000 and 2006 from chicken flocks in the United Kingdom, during studies OZO501 and VMO2200 funded by the Department for Environment, Food and Rural Affairs (9,10,19; N. C. Elviss, L. K. Williams, F. Jorgensen, S. A. Chisholm, A. J. Lawson, C. Swift, R. J. Owen, D. J. Griggs, M. M. Johnson, T. J. Humphrey, and L. J. V. Piddock, submitted for publication). In total, 1,288 Campylobacter isolates were studied; 967 of the isolates were C. jejuni, 319 were C. coli, and 2 were C. lari.…”
Section: Methodsmentioning
confidence: 99%